Effects of feeding raw and treated meskit [Prosopis juliflora (SW.) DC.] pods to Omani Sheep - Al-Khalasi, Said Shannan Ali (2017)
Inclusion of soaked or roasted Meskit pods at high level in concentrate diets for sheep to improve feed intake and reduce production cost has not been studied. The novelty of this study was to evaluate the effect of incorporating soaked or roasted Meskit pods at 50% level in formulated concentrates on digestibility, cost of production, performance, health status and carcass and meat quality of Omani sheep. A locally developed roasting machine was used to roast the Meskit pods at 150 оC for 30 minutes, and tap water was used in soaking the Meskit pods for 24 hours. Formulation of the Meskit pod concentrates was done using, 500 g/kg ground Meskit pods, 240 g/kg wheat bran, 200 g/kg barley, 50 g/kg dried sardine and10 g/kg of salt. All feeds were evaluated using in vitro gas production method. Four groups of intact male Omani sheep at age of 10 months-old with an average of initial weights of 27.43 ± 2.47 kg were used in feeding trial. Each group comprising of six sheep was allocated to receive either 500g/day of commercial concentrate (Oman Feed Mills) or one of the formulated Meskit pods based concentrates; commercial concentrate (CC); roasted Meskit pods based concentrate (ROMPC); raw Meskit pods based concentrate (RMPC) or soaked Meskit pods based concentrate (SMPC). All sheep were allowed free access to Rhodes grass hay and water. Daily feed intakes and bi-weekly body weights were recorded for 84 days. Later, a total of 12 sheep (3 animals per diet) underwent a digestibility experiment comprising of 10 adaptation days and 10 days for sample collection. Blood samples were collected three times during the experimental period, day one, day 42nd and on the last day of the experiment (day 84). At the end of the experiment, the sheep were slaughtered to evaluate carcass and meat quality. The collected blood samples were analysed for hematological and serum biochemistry levels, liver and kidney samples for histopathology to determine the health status of the animals. The outcome of the analysis revealed a higher CP in RMPC (14.69%) and had higher ADF and NDF in ROMPC (18.28% and 34.74%, respectively) in comparison to the rest of Meskit pods based concentrates. The RMPC indicated higher condensed tannin (2.18%) and saponin (4.12%) in comparison to other Meskit pods based concentrates whereas CC revealed non-detectable tannin. In vitro gas production results showed that raw pods (0.087 ml/h) had the lowest gas production compared to treated Meskit pods. There were no signs of illness and microscopic results of kidney and livers samples of sheep did not show any abnormalities. There were no considerable variations of digestibility coefficients of all aspects, and rumen condition had no diets effect with an exception of increased acetic acid in ROMPC group. Roasting of Meskit pods significantly increased feed intake and body weight gain by sheep as compared to use of raw or soaked Meskit pods and were comparable to those fed CC. The carcass characteristics and meat quality indicated no significant differences with an exception that sheep fed with ROMPC and CC had increased carcass weights, and ROMPC fed animals had carcass with higher expressed juice. The use of ROMPC for sheep significantly maximized the profit of the feedlot operation. This study indicated that raw and treated Meskit pods could be used at level of 50% in concentrates for feeding Omani sheep without adverse impacts on health, digestibility, performance or carcass and meat quality and roasting the Meskit pods is highly recommended as a strategy to improve the feed intake and growth rate of Omani sheep and might be an alternative feed compared to the highly priced commercial concentrate.